Antioxidant supplement and sports - Donatucci, B.; Sbardella, D.; Tundo, G. R.; Casasco, M.; Di Daniele, N.; Rogliani, P.; Marini, S. (Medicina dello Sport, 2015)
Antioxidants are largely used to maintain redox homeostasis. Unfortunately, most of the controlled studies demonstrated that, if in vitro these molecules are able to modulate several biochemical parameters, after in vivo administration usually they fail to exert any significant activity both on healthy subjects and patients. The usage of antioxidant supplements is common practice among athletes and is based on the idea that they prevent the negative effects of oxidative stress caused by exercise, and that they promote muscle recovery and improve performance. In this review we discuss and comment main experimental studies in which several antioxidant have been used to modulate sport performances in athletes.